Biogas Dari Limbah Dan Prototype (Bagian 1) - Karsini Karsini (Jurnal Kimia dan Kemasan, 1979)
Since 1977/1978 Industrial Research Institute Jakarta has become actively involved in the planning and operation of biogas plants, which recover meth~ne gas and enriched fertilizer from livestock manure (pig manure) and organic waste. In 1978/1979 there bas been built a biogas digester unit at Kapuk , west Jakarta. And methane gas production has been used for lighting and cooking.